2010
DOI: 10.1002/j.2048-7940.2010.tb00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Access to Cardiac Rehabilitation Among South-Asian Patients by Referral Method: A Qualitative Study

Abstract: People of South‐Asian origin have an increased prevalence of coronary artery disease. Although cardiac rehabilitation (CR) is effective, South Asians are among the least likely people to participate in these programs. Automatic referral increases CR use and may reduce access inequalities. This study qualitatively explored whether CR referral knowledge and access varied among South‐Asian patients. Participants were South‐Asian cardiac patients receiving treatment at hospitals in Ontario, Canada. Each hospital r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 19 publications
(24 reference statements)
0
37
0
1
Order By: Relevance
“…Galdas and Kang () did not report gender differences because none were found. Grewal () and Sloots et al . () questioned the influence of the researcher's gender in data collection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Galdas and Kang () did not report gender differences because none were found. Grewal () and Sloots et al . () questioned the influence of the researcher's gender in data collection.…”
Section: Resultsmentioning
confidence: 99%
“…, Grewal et al . ). Furthermore, we argue in this section that in uptake‐related decisions, women and men may interpret from a gendered perspective what little information they do possess about programmes to support decisions about uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitatative data synthesis System and service barriers affecting CR attendance. A number of studies reported the importance of physician recommendation in the decision to participate in CR, [13][14][15][16][17] particularly when the patient was ambivalent about participating (Figure 2). Some studies identified physicians as recommending against CR.…”
Section: Qualitymentioning
confidence: 99%
“…Historically, South Asians tend to have had low referral rates, uptake and adherence to cardiac rehabilitation (Banerjee, Gupta, & Singh, 2007;Beswick et al, 2004;Galdas & Kang, 2008;Jolly, Greenfield, & Hare, 2004;Scott, Gravely, Sexton, Brzostek, & Brown, 2013), although uptake may vary by country (Rana et al, 2014). A Canadian study (Grewal et al, 2010) exploring South Asian patients' barriers to CR identified a number of factors that might help explain such poor uptake; the importance of in-hospital communication with care providers, providing knowledge of the comprehensive nature of cardiac rehabilitation and the importance of post discharge follow-up and the need to support personal autonomy were identified as important factors. Chauhan, Baker, Lester, and Edwards (2010) in a British study with 20 South Asian participants reported that patients had limited understanding of their condition, had negative experiences of healthcare, valued social networks, held fatalistic health beliefs and identified religious, cultural and practical barriers.…”
Section: What This Paper Addsmentioning
confidence: 99%